2014
DOI: 10.1177/0269881114543721
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tobacco smoke constituents, anabasine and anatabine, on memory and attention in female rats

Abstract: Nicotine has been well characterized to improve memory and attention. Nicotine is the primary, but not only neuroactive compound in tobacco. Other tobacco constituents such as anabasine and anatabine also have agonist actions on nicotinic receptors. The current study investigated the effects of anabasine and anatabine on memory and attention. Adult female Sprague-Dawley rats were trained on a win-shift spatial working and reference memory task in the 16-arm radial maze or a visual signal detection operant task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…Racemic anatabine was marketed as an herbal supplement called Anatabloc by Rock Creek Pharmaceuticals. Several studies supported by this company have shown that anatabine, in addition to its anti-inflammatory actions, has procognitive [40][41][42][43], neuro-protective [44], immune disease modulating [45,46], and smoking cessation actions. Anatabine partially substitutes for nicotine in drug discrimination behavioral assays but does not have the addictive potency of nicotine [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Racemic anatabine was marketed as an herbal supplement called Anatabloc by Rock Creek Pharmaceuticals. Several studies supported by this company have shown that anatabine, in addition to its anti-inflammatory actions, has procognitive [40][41][42][43], neuro-protective [44], immune disease modulating [45,46], and smoking cessation actions. Anatabine partially substitutes for nicotine in drug discrimination behavioral assays but does not have the addictive potency of nicotine [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Nicotine is an agonist of nicotinic acetylcholine receptors (nAChRs) and a major psychoactive component in tobacco smoke (Levin et al , 2014). However, research on the neuroprotective and neurotoxic effects of nicotine in the CNS has been inconclusive (Nie et al , 2013; Nordberg et al , 2002; Picciotto and Zoli, 2008b; Zeng et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, research on the neuroprotective and neurotoxic effects of nicotine in the CNS has been inconclusive (Nie et al , 2013; Nordberg et al , 2002; Picciotto and Zoli, 2008b; Zeng et al , 2001). For example, nicotine has been shown to produce significant improvement in the attention span and memory performance in both human and animal studies (Knott et al , 2012; Levin et al , 2014) and has been implicated in neuroprotective effects against β-amyloid-mediated neurotoxicity as well as the enhanced neuroplasticity in transgenic model for Alzheimer’s disease in mice (Nie et al , 2013). These effects are likely mediated by up-regulation of nAChR expression and decrease in the accumulation of β-amyloid peptide leading to a decrease in neurotoxicity (Kihara et al , 1997; Nordberg et al , 2002; Picciotto and Zoli, 2008b; Zeng et al , 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These substances are considered to improve cognition in terms of memory and attention [8]. In our set up the cognition was assessed using Montreal cognitive assessment.…”
Section: Discussionmentioning
confidence: 99%